Enhancing anemia diagnostics and accessibility in India: a policy recommendation for effective anemia management - Shyamkumar Sriram; Soni Sharma (Frontiers in Health Services)
Anemia remains a major public health issue in India, with a high prevalence among women, children, and vulnerable populations. Current diagnostic methods vary, impacting the accuracy and comparability of data across regions and complicating anemia tracking. Policy proposals include standardizing diagnostic techniques, enhancing non-invasive device accuracy, and expanding access to diagnostic instruments in underprivileged areas. Strengthening anemia data collection and increasing public awareness are essential for effective anemia management.